The Revitalization Movement in the Catholic Church: The Institutional Dilemma of Power - Ebaugh, Helen Rose Fuchs (Sociological analysis, 1991)
Post-Vatican II developments in the Roman Catholic Church are seen as part of an institutional revitalization movement, the basis for which was provided by the Council's reconceptualization of the Church as the “People of God.” The result was a dilemma of authority for the hierarchy as the laity internalized this notion and began to challenge the legitimacy of hierarchic control. Resource mobilization theory is used to detail this process. The consequences of this reconceptualization for Roman Catholicism in the United States were: personalized religion, selective Catholicism, an emphasis on religion as ethnic and cultural identity, and the revitalization of traditional values by means of social support groups in the church. Each of these is discussed briefly.